Sprint running with a body-weight supporting kite reduces ground contact time in well-trained sprinters - Kratky, S.; Müller, E. (The Journal of Strength and Conditioning Research, 2013)
It is well founded that ground contact time is the crucial part of sprinting because the available time window to apply force to the ground diminishes with growing running velocity. In view of this knowledge, the purpose of this study was to investigate the effects of body-weight support during full-effort sprints on ground contact time and selected stride parameters in 19 Austrian male elite sprinters. A kite with a lifting effect combined with a towing system to erase drag was used. The subjects performed flying 20-m sprints under 3 conditions: (a) free sprint; (b) body-weight supported sprint—normal speed (BWS-NS); and (c) body-weight supported sprint—overspeed (BWS-OS). Sprint cycle characteristics were recorded during the high-speed phase by an optical acquisition system. Additionally, running velocity was derived from the 20-m sprint time. Compared with the fastest free sprint, running velocity, step length, and step frequency remained unchanged during BWS-NS, whereas ground contact time decreased (-5.80%), and air time increased (+5.79%) (both p < 0.001). Throughout, BWS-OS ground contact time (-7.66%) was reduced, whereas running velocity (+2.72%), air time (+4.92%), step length (+1.98%) (all p < 0.001), and step frequency (+1.05%; p < 0.01) increased. Compared with BWS-NS, BWS-OS caused an increase in running velocity (+3.33%), step length (+1.92%) (both p < 0.001), and step frequency (+1.37%; p < 0.01), whereas ground contact time was diminished (-1.97%; p < 0.001). In summary, sprinting with a body-weight supporting kite appeared to be a highly specific method to simulate an advanced performance level, indicated by higher running velocities requiring reduced ground contact times. The additional application of an overspeed condition led to a further reduction of ground contact time. Therefore, we recommend body-weight supported sprinting as an additional tool in sprint training.